PENGARUH TANAMAN REFUGIA DAN MACAM VARIETAS JAGUNG (Zea mays L.) TERHADAP SERANGGA TANAH, PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG - Kusuma Rizal Adha; Supriyono Supriyono (Jurnal Ilmiah Hijau Cendekia, 2022)
The purpose of this research is that farmers are expected to get information about soil insects and understand the system of using refugia as a supporter for the development of agricultural commodities for the realization of a sustainable agricultural system based on ecosystem sustainability. The research was carried out from December 2021 to March 2022, which took place in Plaosan Village, Wates District, Kediri Regency. The method used was a factorial randomized block design. The first factor is the difference in corn varieties (J) consisting of three levels, Pertiwi-3, Bisi-18 and Bisi-228. The second factor is the difference in refugia plants (R) consisting of four levels, namely Control, Kenikir, Paper and Marigold. Observations found 26 families consisting of 8 orders. For diversity, evenness and species richness, moderate values ​​were obtained. The results of variance showed that there was no interaction between different varieties with different refugia plant treatments on the number of leaves of corn plants at all ages of observation, but in single factor treatment, differences in varieties showed an effect on the number of leaves of plants at all ages of corn plants. The combination of treatment between varieties and refugia obtained the highest value at an average weight of 376.13 grams of cob, at a weight value of 1000 seeds the highest value was obtained with an average of 306.92 grams and the combination of varieties and refugia treatments obtained the highest potential yield of corn with a value of 11,033. ,33 tons/ha.